2018
DOI: 10.4103/jmau.jmau_22_18
|View full text |Cite
|
Sign up to set email alerts
|

More than an association: Latent toxoplasmosis might provoke a local oxidative stress that triggers the development of bipolar disorder

Abstract: Introduction:Toxoplasma gondii, a common parasitic infection, has a special affinity to the brain. It has a lifelong existence without an apparent clinical disease. While the etiology of bipolar disorder (BD) remains unclear, epidemiological studies suggest a role for infections. Central nervous system is particularly susceptible to oxidative stress (OS) because of its high metabolic rate and its low levels of antioxidant defenses. OS is a contributor to the initiation and progression of many neurological illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
2
6
1
Order By: Relevance
“…Other studies have reported a higher seroprevalence of T. gondii infection in patients suffering from bipolar disorder than in control subjects. These findings have been reported in Saudi Arabia (19), France (20, 32), the United States (22), and Ethiopia (17). In a meta-analysis of 50 studies about the association of seroprevalence of T. gondii infection and psychiatric disorders, researchers found a significant OR with IgG antibodies in bipolar disorder (13).…”
Section: Discussionsupporting
confidence: 76%
“…Other studies have reported a higher seroprevalence of T. gondii infection in patients suffering from bipolar disorder than in control subjects. These findings have been reported in Saudi Arabia (19), France (20, 32), the United States (22), and Ethiopia (17). In a meta-analysis of 50 studies about the association of seroprevalence of T. gondii infection and psychiatric disorders, researchers found a significant OR with IgG antibodies in bipolar disorder (13).…”
Section: Discussionsupporting
confidence: 76%
“…Findings of this report suggest that re-exposure to the parasite Grande et al, 2017), as has been suggested for schizophrenia (Sutterland et al, 2015). Furthermore, the potential of latent toxoplasmosis to provoke the development of bipolar disorder has been suggested (Afifi et al, 2018). The present study showed that both depression and anxiety were more likely to occur in patients with toxoplasmosis than in those without, whereas varying results have been found in the literature.…”
Section: Discussionsupporting
confidence: 62%
“…Findings of this report suggest that re-exposure to the parasite could modify the individual's immune response and reactivate latent toxoplasmosis (Del Grande et al ., 2017), as has been suggested for schizophrenia (Sutterland et al ., 2015). Furthermore, the potential of latent toxoplasmosis to provoke the development of bipolar disorder has been suggested (Afifi et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been contemplated that latent T. gondii may trigger CNS oxidative stress, leading to immune-inflammatory processes that could promote or resemble CNS changes seen in bipolar disorder [ 82 84 ]. In studies conducted by Pearce et al and Hamdani et al, it was found that patients seropositive for T. gondii infection were approximately 2.3- and 2.7-folds more likely to have a history of bipolar disorder type I with manic and depressive symptoms than respondents who tested negative for the T. gondii antibody [ 85 , 86 ].…”
Section: Methodology and Resultsmentioning
confidence: 99%